Optimization of extraction conditions and assessment of antioxidant, α-glucosidase inhibitory and antimicrobial activities of Xanthium strumarium L. fruits. (April 2018) - Ingawale, Amol Subhash; Sadiq, Muhammad Bilal; Nguyen, Loc Thai; Ngan, Tu Bao
Abstract: In this study, Xanthium strumarium L. fruit was extracted and the product obtained was analyzed for its antioxidant, antimicrobial and antidiabetic activities. The effects of solvent (methanol), extraction time and solid/solvent ratios on total phenolic content (TPC), 1, 1-diphenyl-1-picryl-hydrazyl-hydrate (DPPH) radical scavenging activity and the ferric reducing antioxidant power (FRAP) were investigated. The results indicated that optimal methanol concentration, extraction time and solid to solvent ratio were 60%, 30 min and 1:5, respectively. Corresponding TPC, DPPH and FRAP values were 12.1 mg of GAE/g of sample, 72.5% and 92.6 μM of Fe (II)/g of sample, respectively. Methanol concentration and solid to solvent ratio were found to have significant effects on TPC, DPPH and FRAP values. On the other hand, the fruit extracts demonstrated antibacterial activity against Staphyloccocus aureus and Streptococcus agalactiae . When tested for antidiabetic potential, the extract exhibited strong α-glucosidase inhibitory effect with IC50 value of 15.25 µg/ml. Electrochemical measurements were found to be helpful for determining the content as well as redox properties of the extracted compounds. The results could be of significant importance for industrial applications of the extract in novel plant-derived drugs or functional foods. Graphical abstract: Highlights: Extraction of Xanthium strumarium L. fruits was optimized using RSM. Fruit extract presented antioxidant, antibacterial and antidiabetic potentials. The extract exhibited strong antidiabetic effect with IC50 value of 15.25 µg/ml. Electrochemical measurements of extract were correlated with its bioactivities.